Environmental Migrants and Canada’s Refugee Policy - Murray, Sheila (Refuge: Canada's Journal on Refugees, 2011)
Canada is among the world’s foremost refugee resettlement countries and is signatory to international agreements that affirm its commitment to the protection of refugee rights. Asylum seekers come to Canada from around the globe. But as climate change continues to affect growing regions of the world—threatening to create as many as 200 million environmental migrants by the year 2050—Canada has not yet begun to address the issue of climate change migration. In an era defined by a neo-liberal approach to migration issues, and until international actors determine the status of environmental migrants, Canada’s policy response to the looming crisis may be conjectured from an historical review of its refugee policy. This provides an understanding of the various factors, both domestic and international, that may have the greatest influence on Canada’s future refugee policy.